If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -2(7w + -2) + 5w = 2 + 2(3w + -8) Reorder the terms: -2(-2 + 7w) + 5w = 2 + 2(3w + -8) (-2 * -2 + 7w * -2) + 5w = 2 + 2(3w + -8) (4 + -14w) + 5w = 2 + 2(3w + -8) Combine like terms: -14w + 5w = -9w 4 + -9w = 2 + 2(3w + -8) Reorder the terms: 4 + -9w = 2 + 2(-8 + 3w) 4 + -9w = 2 + (-8 * 2 + 3w * 2) 4 + -9w = 2 + (-16 + 6w) Combine like terms: 2 + -16 = -14 4 + -9w = -14 + 6w Solving 4 + -9w = -14 + 6w Solving for variable 'w'. Move all terms containing w to the left, all other terms to the right. Add '-6w' to each side of the equation. 4 + -9w + -6w = -14 + 6w + -6w Combine like terms: -9w + -6w = -15w 4 + -15w = -14 + 6w + -6w Combine like terms: 6w + -6w = 0 4 + -15w = -14 + 0 4 + -15w = -14 Add '-4' to each side of the equation. 4 + -4 + -15w = -14 + -4 Combine like terms: 4 + -4 = 0 0 + -15w = -14 + -4 -15w = -14 + -4 Combine like terms: -14 + -4 = -18 -15w = -18 Divide each side by '-15'. w = 1.2 Simplifying w = 1.2
| q-2r=4 | | 27+5n=7(4n-6) | | 15x+8=25x+12 | | 3y-21=18 | | x=ax+3x | | 0.15b-1=-5.5 | | 368=8(-2+6x) | | 3(x+6)=-3(x-2)+18 | | 2.500(15y+10)-2(4y+7)=0 | | X-(-4)=34 | | b=ax+3x | | 4(x+3)=-2(4x-9)+2x | | 85=-3+2(4-5r) | | 7(a-8)=28-5a | | 9+c=-18 | | -34=-45 | | 4(3x+1)=24 | | 1-5b=2-4b | | 2-5p=22 | | 3x-16=-41+8x | | e+(-4)=7 | | 3x^3+10x^2-4x-35=0 | | x^2+3x^2+2x= | | 3n+2n=5 | | X+-4.2=-3 | | x^5-4x^4+x^3-7x+1=0 | | -91=p-6(-p+7) | | -17x-23x=12x-2 | | -17x-23x=12x-2 | | x^2-x-6%x^2-5x+6 | | f(x)=zx^2+12x+14 | | 2(u-8)-1=-5(-5u+4)-5u |